Father's Role in Early Childhood Parenting: a Seminar in Tanjunganom Village, Rowosari Subdistrict, Kendal Regency - Faiq Ar-Rofi; Aisa Rurkinantia; Habib Hasnan Adzin; Isnaini Zulfa Aprilia; Diva Suci Wulandari; Nadia Muna Erliza; Aura Nabila Deswita Nungtyas; M Reza Nugraha Putra (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The active involvement of both parents in parenting is critical to the development of early childhood. In Indonesia, however, fathers are often less engaged in child-rearing due to the perception that their primary role is to provide financially. This seminar aimed to raise awareness among fathers in Tanjunganom Village, Rowosari Subdistrict, Kendal Regency, about the importance of their involvement in early childhood parenting. The seminar was structured to include presentations, discussions, and ongoing support. The outcomes indicated a significant improvement in fathers’ knowledge and their ability to balance time between work and childcare. Children with more actively engaged fathers exhibited improved social, emotional, and cognitive development. The results reinforce the importance of fathers’ involvement in parenting as a shared responsibility between both parents.